Deprescribing in Older Adults With Cancer and Limited Life Expectancy: An Integrative Review. (January 2022) - Brokaar, Edwin J.; van den Bos, Frederiek; Visser, Loes E.; Portielje, Johanneke E. A.
Polypharmacy is common in older adults with cancer and deprescribing potentially inappropriate medications becomes very relevant when life expectancy decreases due to metastatic disease. Especially preventive medications may no longer be beneficial, because they may decrease quality of life and reduction in morbidity and mortality may be futile. Although deprescribing of preventive medication is common in the last period of life, it is still unusual during active cancer treatment for advanced disease, although life expectancy is often limited to less than 1 to 2 years in that stage. We performed a systematic search of the literature in Pubmed and Embase on the discontinuation of commonly utilized groups of preventive medication and evaluated the evidence of potential benefits and harms in patients aged 65 years or older with cancer and a limited life expectancy (LLE). From 21 included studies, it can be concluded that deprescribing lipid lowering drugs, antihypertensive drugs, osteoporosis drugs and antihyperglycemic drugs is feasible in a considerable part of patients with a LLE. Discontinuation may be performed safely, without the occurrence of serious adverse events or decrease of survival. The only study that addressed quality of life after deprescribing showed that discontinuation of statins improves quality of life in patients with a LLE. Recurrence of symptoms requiring reintroduction occurred in 0-13% of patients on antihyperglycemic treatment and 8-60% of patients using antihypertensive drugs. In order to reduce pill burden and futile treatment clinicians should discuss deprescribing of preventive medication with older patients with advanced cancer and a LLE.